From Communicative Action to Linguistic Capital: Arabic 'āmiyyah as an Economic Communication Strategy in Multicultural Competition in Pasuruan - Dewi Masita; Wilda Rihlasyitha (PT. Caesarindo Triloka Persada, 2026)
In Indonesia's local economy, language plays a crucial role not only as a medium of communication but also as a strategic resource for fostering trust, building social networks, and creating economic opportunities. While existing research on Arabic in Indonesia predominantly examines its role in religious, educational, and diplomatic settings, its use in daily commercial interactions, particularly in local markets, has remained underexplored. This study addresses this gap by investigating the role of Arabic ‘āmiyyah as both a form of communicative action and a type of linguistic capital in the multicultural marketplace of Pasuruan. Using a qualitative sociolinguistic ethnographic approach, the research was conducted in the Kauman and Jalan Jawa areas of Pasuruan City. Participants included Arab Jamaah traders, customers from Arab, Javanese, and Chinese backgrounds, as well as key informants. Data were gathered through participant observation, in-depth interviews, and recordings of market interactions, and analyzed using discourse and thematic analysis. The findings reveal that Arabic ‘āmiyyah, particularly through code-switching and lexical choices, serves as a key tool for building trust, enhancing customer loyalty, and generating economic value. This highlights the significance of language as a vital microeconomic resource in a multicultural economic context, thereby contributing to the broader understanding of linguistic capital in economic communication.